INTEGRATION OF HETEROGENEOUS KNOWLEDGE IN INTELLECTUAL INFORMATION SYSTEMS BASED ON MULTI-AGENT SIMULATION - Yury A. Kravchenko; Markov V. Vladimir (Открытое образование (Москва), 2016)
The article considers the problem of creating a multi-agent models integrating heterogeneous prior knowledge about the subject of research in order to ensure the possibility of combining the analytical information from different domains in intellectual information systems. The solution of this problem is demonstrated by the example of the method of students cognitive personality traits researches results integration and artificial intelligence technologies to create cognitive styles of diagnostic systems with the further individual paths, education models and reference groups development, based on the theory of multi-agent systems. The considered models’ investigation was conducted based on apparatus simulation of Petri nets.